Synthesis of 9, 9′‐Spirobifluorenes and 4, 5‐Diaza‐9, 9′‐spirobifluorenes and Their Application as Affinity Materials for Quartz Crystal Microbalances. Issue 5 (16th May 2017) - Stobe, Caroline; Pyka, Isabella; Linke, Alexander; Müller, Sarah; Schnakenburg, Gregor; Waldvogel, Siegfried R.; Lützen, Arne
Abstract: Two different classes of aza analogues of 9, 9′‐spirobifluorenes have been synthesized. These were obtained by either furnishing the spirobifluorene with additional pyridyl moieties or by installing the aza function directly into the spirobifluorene core. These structurally rigid compounds were then evaluated as affinity materials for quartz crystal microbalances and proved to be highly potent for the detection of volatile organic compounds. Abstract : Making contact : The cross‐like architectures of spirobifluorene are capable of interacting with volatile molecules, leading to special host–guest interactions that can be investigated by quartz crystal microbalances (see figure). Unique affinity materials with tailor‐made properties are generated by combining spirobifluorene building blocks with pyridyl moieties or by installing aza functions directly into the spirobifluorenes.